2022
DOI: 10.3389/fvets.2022.862092
|View full text |Cite
|
Sign up to set email alerts
|

Non-native Nematode Ashworthius sidemi Currently Dominates the Abomasal Parasite Community of Cervid Hosts in the Czech Republic

Abstract: Ashworthius sidemi is an abomasal nematode typical for Asiatic cervids such as sambar (Rusa unicolor) or sika deer (Cervus nippon). This non-native parasite was introduced into Europe via sika deer in the late 19th and early 20th centuries. The current dynamic spread of this parasite amongst autochthonous wild cervids occurs independently of human activities, and A. sidemi has a negative impact on the health of wild ruminants and may pose a threat to the conservation of endangered wild ungulates and to livesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…In contrast, our results suggest that under the current Central European climate and management conditions at the study location, A. sidemi egg shedding may occur almost year-round from April to January. This finding is consistent with previous studies conducted in the CR that reported the occurrence of A. sidemi adults in wild ruminants and lack of hypobiosis during the winter (15,21). A possible explanation for this shift could be recent higher temperatures that are more favorable for the parasite development than those prevailing during investigations of A. sidemi seasonal dynamics fifteen years ago or earlier.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, our results suggest that under the current Central European climate and management conditions at the study location, A. sidemi egg shedding may occur almost year-round from April to January. This finding is consistent with previous studies conducted in the CR that reported the occurrence of A. sidemi adults in wild ruminants and lack of hypobiosis during the winter (15,21). A possible explanation for this shift could be recent higher temperatures that are more favorable for the parasite development than those prevailing during investigations of A. sidemi seasonal dynamics fifteen years ago or earlier.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been previously published (20); only larvae and juveniles of A. sidemi were recovered from the abomasa of sika deer and Maral deer during autumn and winter in the Russian Far East. In contrast to the above mentioned studies, only negligible importance of hypobiosis has been detected in the Czech Republic (CR), indicating a possible modification of seasonal patterns in A. sidemi (15,21). Seasonal dynamics of trichostrongylids can differ based on the climate conditions in different regions and may also shift over time due to global climate changes (22,23).…”
Section: Introductionmentioning
confidence: 87%
“…Wild cervids are known to have a relatively effective immunity against gastro-intestinal nematodes. This phenomenon is attributed to the secondary plant metabolites, which characterise the normal diet of these browser and intermediate grazer ruminants (Magdálek et al 2022). Our study aimed to determine those feed components which could be potent against Haemonchus contortus the most threatening parasite in the small ruminant sector (Adduci et al 2022).…”
Section: Natural Dewormers Of Cervids: Effect Of Amber and Acorns On ...mentioning
confidence: 99%